PENGARUH GUIDED IMAGERY TERHADAP NYERI AKIBAT PENUSUKAN AKSES VASKULER PASIEN HEMODIALISIS DI UNIT HEMODIALISIS RUMAH SAKIT UMUM DAERAH HARAPAN INSAN SENDAWAR - Septina Neli; frana andrianur; Ismansyah Ismansyah (MNJ (Mahakam Nursing Journal), 2023)
Pain due to vascular access stabbing in hemodiasis patients poses a problem. Guided imagery is a nursing service to encourage patients to make fantasies by visualizing situations that the patient likes, which is expected to reduce the pain they experience.. The research design used a quasi-experimental design with one group pretest posttest with control group. Respondents were taken by consecutive sampling of 30 patients in the hemodialysis room at Harapan Insan Sendawar Hospital. Data was collected with observation sheets. Data analysis used the Mann Whitney test. The results showed that there were differences in the intervention and control groups after being given guided imagery on the pain score (p = 0.000), so that the hypothesis Ha was accepted and Ho was rejected. Decreased pain scale from 7.67 to 5.53 after getting guided imagery techniques. The instruments used to measure differences in this study are standard, valid and realible. The provision of guided imagery techniques has been shown to reduce the pain scale in patients who had vascular access punctured at the Hemodialysis Unit at Harapan Insan Sendawar General Hospital. Regular exercise and concentration will be maximized in an effort to reduce pain.